Comparative Genomics and In Vitro Plant Growth Promotion and Biocontrol Traits of Lactic Acid Bacteria from the Wheat Rhizosphere - Sabrina Strafella (Microorganisms, 2021)
This study aimed to isolate lactic acid bacteria (LAB) from wheat rhizosphere, to characterize their in vitro plant growth promoting activities and to differentiate plant-associated LAB from those associated with foods or human disease through comparative genomic analysis. Lactococcus lactis subsp. lactis and Enterococcus faecium were isolated using de Man-Rogosa-Sharpe (MRS) and Glucose Yeast Peptone (GYP) as enrichment culture media. Comparative genomic analyses showed that plant-associated LAB strains were enriched in genes coding for bacteriocin production when compared to strains from other ecosystems. Isolates o f L. lactis and E. faecium did not produce physiologically relevant concentrations of the phyto-hormone indolacetic acid. All isolates solubilized high amount of phosphate and 12 of 16 strains solubilized potassium. E. faecium LB5, L. lactis LB6, LB7, and LB9 inhibited the plant pathogenic Fusarium graminearum to the same extent as two strains of Bacillus sp. However, the antifungal activity of the abovementioned LAB strains depended on the medium of cultivation and a low pH while antifungal activity of Bacillus spp. was independent of the growth medium and likely relates to antifungal lipopeptides. This study showed the potential of rhizospheric LAB for future application as biofertilizers in agriculture.